Probabilistic Theory of Efficient Internalization of Nanoparticles at Targeted Drug Delivery Strategies - Nieto-Chaupis, Huber (2020)
In this paper, the action that lead to an efficiently Targeted Drug Delivery through the process of internalization is studied. Although one can expects that the probability to reach a target is, however in praxis this might not be clean in the sense that the surface of nanoparticles composed by ions exerts electrical interaction with charged electrically compounds around. The action to internalize the nanoparticle acquires relevance when one expects either electrical attraction or repulsion between nanoparticle and tumor or target tissue. This paper tries to model this through the concept of overlapping wave functions. The results would indicate that quantum numbers might be critic at the action of internalization.